Validity of the Elite HRV smartphone application for examining heart rate variability in a field-based setting - Perrotta, A. S.; Jeklin, A. T.; Hives, B. A.; Meanwell, L. E.; Warburton, D. E. R. (The Journal of Strength and Conditioning Research, 2017)
The introduction of smartphone applications has allowed athletes and practitioners to record and store R-R intervals on smartphones for immediate heart rate variability (HRV) analysis. This user-friendly option should be validated in the effort to provide practitioners confidence when monitoring their athletes before implementing such equipment. The objective of this investigation was to examine the relationship and validity between a vagal-related HRV index, rMSSD, when derived from a smartphone application accessible with most operating systems against a frequently used computer software program, Kubios HRV 2.2. R-R intervals were recorded immediately upon awakening over 14 consecutive days using the Elite HRV smartphone application. R-R recordings were then exported into Kubios HRV 2.2 for analysis. The relationship and levels of agreement between rMSSDln derived from Elite HRV and Kubios HRV 2.2 was examined using a Pearson product-moment correlation and a Bland-Altman Plot. An extremely large relationship was identified (r = 0.92; p < 0.0001; confidence interval [CI] 95% = 0.90-0.93). A total of 6.4% of the residuals fell outside the 1.96 ± SD (CI 95% = -12.0 to 7.0%) limits of agreement. A negative bias was observed (mean: -2.7%; CI 95% = -3.10 to -2.30%), whose CI 95% failed to fall within the line of equality. Our observations demonstrated differences between the two sources of HRV analysis. However, further research is warranted, as this smartphone HRV application may offer a reliable platform when assessing parasympathetic modulation.